2019
DOI: 10.1111/1440-1681.13172
|View full text |Cite
|
Sign up to set email alerts
|

Placental mitochondria and reactive oxygen species in the physiology and pathophysiology of pregnancy

Abstract: Mitochondria are central to cell function. The placenta forms the interface between maternal and fetal systems, and placental mitochondria have critical roles in maintaining pregnancy. The placenta is unusual in having two adjacent cell layers (cytotrophoblasts and the syncytiotrophoblast) with vastly different mitochondria that have distinct functions in health and disease. Mitochondria both produce the majority of reactive oxygen species (ROS), and are sensitive to ROS. ROS are important in allowing cells to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 108 publications
1
50
0
Order By: Relevance
“…Mitochondrial SOD activity is reduced in pre-term pre-eclamptic placentae, compared to pre-term controls [ 38 ]. Furthermore, mitochondrial fusion/fission seems to be impaired in PE, although this relationship is complex and still poorly understood [ 43 ]; some findings have indicated a pro-fusion state in severe cases of PE [ 42 ], while other research has shown a more pro-fission state [ 41 , 44 ]. Additionally, there is a decrease in TFAM (Mitochondrial Transcription Factor A) expression [ 42 ] and reduced expression of proteins involved in mitochondrial biogenesis, such as PGC-1α (peroxisome proliferator-activated receptor-gamma coactivator 1-α) and SIRT3 (Sirtuin 3) [ 41 ].…”
Section: Mitochondrial Function In Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondrial SOD activity is reduced in pre-term pre-eclamptic placentae, compared to pre-term controls [ 38 ]. Furthermore, mitochondrial fusion/fission seems to be impaired in PE, although this relationship is complex and still poorly understood [ 43 ]; some findings have indicated a pro-fusion state in severe cases of PE [ 42 ], while other research has shown a more pro-fission state [ 41 , 44 ]. Additionally, there is a decrease in TFAM (Mitochondrial Transcription Factor A) expression [ 42 ] and reduced expression of proteins involved in mitochondrial biogenesis, such as PGC-1α (peroxisome proliferator-activated receptor-gamma coactivator 1-α) and SIRT3 (Sirtuin 3) [ 41 ].…”
Section: Mitochondrial Function In Pregnancymentioning
confidence: 99%
“…Additionally, there is a decrease in TFAM (Mitochondrial Transcription Factor A) expression [ 42 ] and reduced expression of proteins involved in mitochondrial biogenesis, such as PGC-1α (peroxisome proliferator-activated receptor-gamma coactivator 1-α) and SIRT3 (Sirtuin 3) [ 41 ]. Alterations in mitochondrial content may help to increase bioenergetic efficiency under adverse conditions [ 43 ]. mtDNA copy number has been inversely correlated with gestational age and birth weight [ 45 ].…”
Section: Mitochondrial Function In Pregnancymentioning
confidence: 99%
“…Mitochondria are dynamic organelles constantly changing through mitochondrial fission and fusion pathways (Fisher et al . 2019 b ), responsible for the homeostatic maintenance of many cellular functions that are crucial for pregnancy. These include regulation of metabolism and nutrient availability, ATP generation through oxidative phosphorylation, generation of reactive oxygen species and hormone synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…[ 8 , [31] , [32] , [33] ]). They continue to do so throughout human development, starting from a gleam in your fathers’ eye, leading to fertilization and all that follows [ 8 , [34] , [35] , [36] , [37] , [38] , [39] ]; I have attempted to summarize this in Fig. 4 .…”
Section: Hydrogen Peroxide Is Ubiquitousmentioning
confidence: 99%
“…4 A ROS view of the human life cycle. ROS are essential for all aspects of the human life cycle, from conception and development until ageing and death [ 8 , [11] , [12] , [13] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] ]. There is a fine balance between their essentiality and the ability of too many of them to cause harm.…”
Section: Hydrogen Peroxide Is Ubiquitousmentioning
confidence: 99%